Folding of graphene slit like pore walls—a simple method of improving CO2 separation from mixtures with CH4 or N2 - Furmaniak, S.; Terzyk, A.; Gauden, P.; Kowalczyk, Poitr; Harris, P. (Institute of Physics Publishing Ltd., 2014)
We report for the first time a detailed procedure for creating a simulation model of energetically stable, folded graphene-like pores and simulation results of CO2/CH4 and CO2/N2 separation using these structures. We show that folding of graphene structures is a very promising method to improve the separation of CO2 from mixtures with CH4 and N2. The separation properties of the analysed materials are compared with carbon nanotubes having similar diameters or S/V ratio. The presented results have potential importance in the field of CO2 capture and sequestration.